Applying an agricultural ontology to web-based applications. (2nd June 2009) - Maliappis, Michael T.
Despite the growing number of ontologies available online, their range of application in real-world projects is comparatively limited. This paper describes the construction of an ontology concerning the horticultural domain of agriculture, and examines its usage in particular application areas. The proposed ontology is used: as a refining and classification tool facilitating indexing and searching processes in a repository environment; as a domain model for a rule knowledge-base construction. A prototype web application has been developed to investigate the usefulness of ontology and examine several software development tools.